The math book from Pythagoras to the 57th dimension, 250 milestones in the history of mathematics - Pickover, Clifford A. (New York, NY Sterling Pub., 2009)
This book covers 250 milestones in mathematical history, beginning millions of years ago with ancient "ant odometers" and moving through time to our modern-day quest for new dimensions.
Includes bibliographical references (p. 518-525) and index.
Keywords: Mathematics -- History